Pengaruh Konsentrasi NaOH pada Pembuatan Kertas dari Serat Daun Nanas dan Daun Pandan Duri - Nina Hartati; Salmira Salmira; Edi Kurniawan; Anjar Siti Mashitoh; Meyci Trisna; Ayu Syufiatun Br Tarigan (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
This research was conducted to determine the physical characteristics of paper made from a mixture of pineapple leaf fiber and thorny pandan leaf fiber as an environmentally friendly alternative raw material. The research method employed was an experimental design with variations in material composition, specifically 8:2, 6:4, 4:6, dan 2:8, which represent the ratio of pineapple leaf fiber to thorny pandan leaf fiber. The papermaking process began with cooking using a sodium hydroxide (NaOH) solution at concentrations of 8%, 10%, and 13% at a temperature of 100 °C. Subsequently, a bleaching stage was performed using kaolin clay (5%) dissolved in 100 mL of distilled water, which was then mixed evenly using a blender. The resulting pulp was filtered, dried, and formed into paper sheets. The research findings indicate that the highest cellulose content, measuring 99,33%, was obtained at the 2:8 composition, while the lowest content, measuring 60%, was found at the 6:4 composition. The maximum grammage reached 117 g/m² and the maximum thickness was 1,21 mm, obtained from the 2:8 and 8:2 compositions, respectively. Meanwhile, the highest tensile strength value, recorded at 4,200823 kN/m was observed in the 8:2 composition. Based on these results, the paper produced demonstrates the potential to comply with the requirements stipulated in SNI 8218:2015.